An exploratory study of Malaysian women entrepreneurs: what drives them into business / Laila Kamaruddin ... [et al.] - Kamaruddin, Laila; Arshad, Azlin Shafinaz; Osman, Che Asniza; Buyong, Siti Zahrah (2018)
A decision to venture into business is a big and difficult decision that must be made by women as there are many factors that need to be considered. This study focuses on three factors (economic, legal and administrative, and socio-cultural) to determine the drivers which propel Malaysian women entrepreneurs to venture into business. Survey questionnaire was adopted in this exploratory study using convenience sampling method. Descriptive studies as well as normality and reliability analyses were used to analyse the data. The study found women entrepreneurs agreed that social and cultural factors are very strong reasons in driving Malaysian women entrepreneurs to venture into business. This is followed by economic factors, followed by legal and administrative factors. The findings of the study can serve as a guideline to identify assistance, programs and activities that would create more women entrepreneurs and at the same grow their business to the next level. Recommendations for future researchers have been put forward at the end of this paper.